COMORBIDITY OF DYSCALCULIA AND OTHER LEARNING DIFFICULTIES: A META-ANALYTIC AND BIBLIOMETRIC REVIEW - Darmiyati, Darmiyati; Ridhaningtyas, Latifa Putri (JURNAL EDUSCIENCE, 2025)
Purpose – This study aims to analyze the strength of the relationship between dyscalculia and other learning disabilities in elementary school students and identify emerging research trends and themes in the literature on this topic. Dyscalculia is a specific learning disorder that affects arithmetic and numerical processing and is associated with other rare disorders such as dyslexia and attention deficit hyperactivity disorder (ADHD). These problems exacerbate the learning challenges and necessitate an integrated approach to teaching and learning.Methodology – This study employed a systematic review, incorporating meta-analysis and a literature review. Meta-analysis: Data were obtained from six studies that met specific inclusion criteria and focused on students aged 6 to 12 years diagnosed with dyslexia and at least one other learning disorder. A literature search was conducted for 191 scientific articles published between 2020 and 2025 in major academic databases (Scopus, Web of Science, ERIC, and PubMed).Findings – The results of this study showed a high correlation between dyslexia and other learning disabilities, ranging from 0.34 to 0.67. The literature review focused on the following key topics: (1) dyslexia and dyslexia comorbidity, (2) studies identifying learning disabilities, and (3) psychological approaches and treatments. This should be considered a positive value.Contribution – This study offers a comprehensive review of research on the etiology of dyslexia and other learning disabilities, highlighting recent advances in the field. The author presents a multimodal model that draws on existing neuroscience and educational principles.